Physiology of pregnancy. Issue 7 (July 2016) - Talbot, Laura; Maclennan, Kirsty
Abstract: During pregnancy, maternal physiology undergoes continual adaptation. These, often interlinked, changes affect all the body systems and are effected by the hormonal influences of the placenta and mechanical adaptations required to accommodate the growing fetus. These expected physiological changes can lead to decompensation in parturients with pre-existing co-morbidities or unmasking of pre-pregnancy disease. A sound knowledge of the expected maternal changes is essential to enable accurate interpretation of physiological and laboratory parameters and implementation of care plans to reduce complications.